Benign Endobronchial Tumors: A Clinicopathologic Review - Insler, Joshua E.; Seder, Christopher W.; Furlan, Karina; Mir, Fatima; Reddy, Vijaya B.; Gattuso, Paolo (Frontiers in Surgery, 2021)
Abstract Purpose: Benign endobronchial tumors are rare entities that can be difficult to diagnose because they often present with nonspecific symptoms and vague radiographic findings. The current study reviews the clinical, radiologic and pathologic features, diagnosis, and treatment of patients with benign endobronchial tumors. Methods: We examined the charts of all patients who presented with biopsy-proven benign endobronchial tumors at a tertiary-care academic medical center between 1993 and 2018. Pertinent clinicopathologic and radiologic data were analyzed, with particular attention paid to treatment modalities and mean overall patient survival. Results: A total of 28 cases were identified. The most common benign neoplasm was hamartoma (37%), followed by lipoma (19%), squamous papilloma (11%), pleomorphic adenoma (7%), mucin gland adenoma (7%), papillary adenoma (3%), hemangioma (3%), neurofibroma (3%), leiomyoma (3%), and papillomatosis (3%). Cough (58%), shortness of breath (44%), and hemoptysis (15%) were the most frequent presentations. Most cases demonstrated well-defined submucosal or pedunculated endobronchial lesions with segmental pneumonia or atelectasis on imaging. Histologic diagnosis was obtained by endobronchial resection in 43% of patients, thoracoscopic lobectomy in 36%, endobronchial biopsy in 18%, and thoracoscopic wedge resections in 3%. All procedures were performed with no intraoperative or in-hospital deaths (mean overall survival: 20.2 years). Conclusion: Benign endobronchial tumors typically present as well-defined submucosal and/or pedunculated lesions, and may lead to post-obstructive complications. Endobronchial resection is the preferred strategy for diagnosis and treatment of these tumors.